Tindakan Ekonomi: Antara Ruang Rasionalitas dan Ruang Religiusitas dalam Perspektif Sosiologi dan Filsafat Sosial - Azizah, Siti (The Sociology of Islam, 2024)
This article analyzes human economic behavior as social beings through two seemingly opposing perspectives: the utilitarian perspective and the embeddedness perspective. The utilitarian perspective posits that economic actions are carried out rationally based on economic principles, falling into the realm of rationality in philosophical studies. Conversely, the embeddedness perspective argues that economic actions are always tied to social contexts such as norms, habits, rules, traditions, and religion, making it impossible for economic actions to be detached from the realm of religiosity. Since humans live in a religious environment, economic actions must adhere to religious values. This article focuses on economic actions as texts or social realities and how the realms of rationality and religiosity can find common ground. Using a literature review method and a philosophical approach, this article collects data through library research techniques and analyzes it using qualitative descriptive analysis and comparative analysis techniques. In the realm of rationality, human economic actions are inseparable from the nature of intellect, where economic actors act according to the logic of their interests. Economic behavior is considered rational if it aligns with the desired logical standards. On the other hand, in the realm of religiosity, humans as moral beings are influenced by their religious character, which impacts their economic actions. This article emphasizes that the analysis of economic actions exists simultaneously in the realms of rationality and religiosity, without being treated as a dichotomy. Economic activities require rationality to maximize efforts but also need strong moral values as an instrument.